2021
DOI: 10.3389/fmed.2021.722758
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Microcirculation and Vascular Hemodynamics in Relation to Macrocirculation in Patients With Systemic Lupus Erythematosus

Abstract: Introduction: Systemic lupus erythematosus (SLE) is associated with premature cardiovascular disease (CVD) and mortality, unexplained by traditional risk factors. Impairment of microcirculation and vascular hemodynamics may represent early signs of vascular affection. We hypothesized that studies of microcirculation and pulse waves may provide additional information, compared to ultrasound (US) alone, for the detection of early vascular disease in SLE.Methods: Sixty well-characterized SLE-patients (52 women, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In a former study, Aix turned out to be related to organ damage measured by Systemic Lupus International Collaborative Clinics (SLICC) index in young women diagnosed with SLE without significant organ damage [ 16 ]. In another study, higher Aix was reported in a middle-aged SLE cohort, and Aix correlated with IMT in the common carotid artery, common femoral artery, and internal carotid artery [ 36 ]. A recent meta-analysis comprising 49 studies also showed increased Aix in patients with SLE compared to healthy controls [ 37 ], which may also underline the importance of measuring Aix.…”
Section: Discussionmentioning
confidence: 99%
“…In a former study, Aix turned out to be related to organ damage measured by Systemic Lupus International Collaborative Clinics (SLICC) index in young women diagnosed with SLE without significant organ damage [ 16 ]. In another study, higher Aix was reported in a middle-aged SLE cohort, and Aix correlated with IMT in the common carotid artery, common femoral artery, and internal carotid artery [ 36 ]. A recent meta-analysis comprising 49 studies also showed increased Aix in patients with SLE compared to healthy controls [ 37 ], which may also underline the importance of measuring Aix.…”
Section: Discussionmentioning
confidence: 99%
“…The system has been used to study microcirculatory perfusion in the Swedish Cardiopulmonary bioimage Study (SCAPIS), a large population-based cohort of men and women aged 50–65 years ( Jonasson et al, 2020 ). The method can differ between normal and disturbed microcirculatory flow in the skin ( Jonasson et al, 2017 ; Svensson et al, 2021 ; Jonasson et al, 2022 ), and the method has previously not been used in TAK.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave analysis (PWA) was performed with applanation tonometry (SphygmoCor ® system, model MM3, AtCor Medical, Sydney, Australia) in both arms in TAK and in the right arm in controls. The procedure of the AIx measurements has been described previously ( Svensson et al, 2021 ). Augmentation index adjusted to heart rate 75 (AIx75) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 10% of all patients with SLE have accelerated atherosclerosis development; inflammation in small, medium, and large vessels; and impaired endothelium-dependent relaxation compared with age-matched controls (3,(42)(43)(44)(45)(46). Multiple clinical studies implicate dyslipidemia and clotting factors in the association between CVD and SLE (5,43,47).…”
Section: Vascularmentioning
confidence: 99%